ANTICOAGULANT THERAPY FOR CORRECTION OF HEMOREOLOGIC PARAMETERS IN CHILDREN WITH PERTHES DISEASE - I.V. Kirgizov; N.N. Kulikov; V.P. Sinyuk; I.A. Shishkin (Педиатрическая фармакология)
The analysis of hemorheological indications at 35 children with II stage of Perthes disease in early school age was made in this paper. The correction methods of hemorheological disorders in case of Perthes disease and way of modern adequate medicament treatment that make the prognosis of disease more predictable and controllable were presented in this work. Key words: Perthes disease, hemostasis, dopplerography, treatment, children. (Pediatric Pharmacology. – 2010; 7(1):72-75)